1990
DOI: 10.1002/ajpa.1330820111
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies among the Nagas and Hmars of eastern India

Abstract: A total of 148 Nagas (65 urban and 83 rural) and 81 Hmars from northeastern India were tested for 15 blood genetic markers. Both the Nagas and Hmars lacked haemoglobin variants and G6PD deficiency and had a high frequency of PGDC. This may be attributed to selective pressures operating at these loci. Genetic distance estimates using 41 alleles at 11 polymorphic loci showed appreciable heterogeneity between the urban and rural Nagas that were in line with the differences in gene frequencies. Considerable geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Meitei are presumably formed by the admixture of Koomal, Looang, Moirang and Meitei, all of whom are reported to have arrived at different periods of time, coming from different directions and now represent the clans of the community [23]. While the Naga are the indigenous tribal population of Manipur, they belong to the Naga-Kuki-Chin group of the Tibeto-Burman linguistic family and are believed to have migrated to Manipur probably between 300 and 400 years ago from Burma [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Meitei are presumably formed by the admixture of Koomal, Looang, Moirang and Meitei, all of whom are reported to have arrived at different periods of time, coming from different directions and now represent the clans of the community [23]. While the Naga are the indigenous tribal population of Manipur, they belong to the Naga-Kuki-Chin group of the Tibeto-Burman linguistic family and are believed to have migrated to Manipur probably between 300 and 400 years ago from Burma [26]. …”
Section: Methodsmentioning
confidence: 99%
“…These three blood group systems are quite useful for studying population affinities on account of their high polymorphic content. The populations included were Khmer, Vietnamese, Chinese-1 (Mainland Chinese, mainly Han), Thai, Filipino, Indonesian (Bali), Burmese, Malay-M (mainland Malaysia), Chinese-2 (Singapore), Malay-S (Singapore), Munda, Tibetan, Sikkimese, Bhutanese, Nepalese, Santal, Khasi, Meities, Ahoms, Negritos, and Toba Batak (Nakajima et al, 1963;Chandanayingyong et al, 1967;Mya-Tu et al, 1971;Blake et al, 1973;Hawkins et al, 1973;Hawkins, 1974;Bhattacharjee, 1975;Mourant et al, 1976;Breguet et al, 1982a,b;Windhof and Walter, 1983;Das et al, 1985;Singh et al, 1986;Hoang et al, 1987;Mukherjee et al, 1987;Saha, 1987Saha, , 1989Roychoudhury and Nei, 1988;Saha and Tay, 1990). All populations except the last two, Negrito and Batak, are regarded as Mongoloid.…”
Section: Genetic Affinities Of the Khmersmentioning
confidence: 93%
“…Recent studies have shown that modern handheld glucose measuring devices have excellent technical characteristics and yield results that are similar to the reference laboratory methods. Furthermore, various studies have reported that capillary glucose measurements are as suitable as venous glucose measurements in the diagnosis and detection of type 2 DM in epidemiological studies and may be cost effective in the implementation of pre-screening procedures [16][17][18][19][20][21][22]. The American Diabetes Association (ADA) recommends screening for Type 2 DM by using a verbal or written questionnaire to select high-risk individuals to increase the costeffectiveness of testing undiagnosed individuals [23].…”
Section: Methodsmentioning
confidence: 99%